Resting pulse rate among adolescents: the 11-year follow-up of the 1993 Pelotas (Brazil) birth cohort study Frequência do pulso de repouso em adolescentes: a visita de 11 anos da coorte de nascimentos de Pelotas, Rio Grande do Sul, Brasil, 1993 - Pedro C. Hallal; Ana M. B. Menezes; Andréa D. Bertoldi; Samuel C. Dumith; Cora Luiza Araújo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The aim of this study was to describe resting pulse rate and associated factors among adolescents. This was a cross-sectional analysis nested in a prospective cohort study, including 4,452 adolescents born in Pelotas, Rio Grande do Sul State, Brazil in 1993, representing 87.5% of the original cohort. Pulse rate was measured with an electronic device at the beginning and end of the interview, and the mean value was used in the analyses. Mean pulse rate was 78.4bpm (SD = 11.0) in the total sample, 76.5bpm (SD = 10.7) in boys, and 80.2bpm (SD = 10.9; p < 0.001) in girls. Black adolescents showed lower mean pulse rates. There was a direct association between pulse rate and blood pressure. Physical activity was inversely associated with pulse rate in the crude analysis only. Elevated pulse rate is strongly associated with high blood pressure, and both variables are predictors of risk of chronic disease in adulthood. O objetivo do estudo foi descrever a freqüência do pulso de repouso em adolescentes e avaliar variáveis associadas. Trata-se de análise transversal aninhada a um estudo de coorte prospectivo, incluindo 4.452 adolescentes nascidos em Pelotas, Rio Grande do Sul, Brasil, em 1993, os quais representam 87,5% da coorte original. A freqüência do pulso foi mensurada no início e ao final da entrevista com aparelho digital, sendo o valor médio utilizado nas análises. O valor médio da freqüência do pulso foi de 78,4bpm (DP = 11,0), sendo de 76,5bpm (DP = 10,7) nos meninos e 80,2bpm (DP = 10,9; p < 0,001) nas meninas. Os adolescentes com pele preta apresentaram valores mais baixos da freqüência do pulso. Houve uma forte associação positiva entre pressão arterial e freqüência do pulso. O escore de atividade física associou-se inversamente com a freqüência do pulso somente na análise bruta. Valores elevados de freqüência do pulso estão fortemente relacionados com valores elevados de pressão arterial, sendo ambas variáveis preditoras do risco de doenças crônicas na vida adulta.